(untitled) (Scientific journal of the Fergana State University, 2026)
The article analyzes the life, professional activity, and scholarly legacy of Leonid Mikhailovich Landa (1921–1971), a researcher who played a significant role in the development of Uzbek historiography and archival studies. The study is based on materials from the scholar’s personal collection (R-2823), preserved in the National Archive of Uzbekistan. It examines Landa’s works devoted to the history of the Soviet period, historical and biographical research, as well as his contribution to source studies, archival science, and historiography. Special attention is given to the reference materials and the guide “Central State Archive of the Uzbek SSR: Department of the Funds of the October Revolution and Socialist Construction”, prepared under the editorship of L.M. Landa.